2006
DOI: 10.1242/jeb.02527
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical adaptability of a sponge extracellular matrix: evidence for cellular control of mesohyl stiffness inChondrosia reniformisNardo

Abstract: SUMMARY The marine sponge Chondrosia reniformis Nardo consists largely of a collagenous tissue, the mesohyl, which confers a cartilaginous consistency on the whole animal. This investigation was prompted by the incidental observation that, despite a paucity of potentially contractile elements in the mesohyl, intact C. reniformis stiffen noticeably when touched. By measuring the deflection under gravity of beam-shaped tissue samples, it was demonstrated that the flexural stiffness of the mesohyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…The first ultrastructural studies have in principle shown some fibrillar forms (Heinemann et al 2007;Garrone et al 1975), and some recent findings have demonstrated other peculiarities of C. reniformis collagens, including the ability of mesohyl cells to affect collagen density. This process modifies directly extracellular macromolecules or the interactions between them, comparable with the dynamics known for the mutable collagenous tissue of echinoderms (Wilkie et al 2006). These peculiarities allow a very dynamic behavior of this species that can move or drop from its substratum, showing disarranged and separated fiber bundles, and the interfibrillar filamentous material that becomes markedly disorganized and rarefied (Bonasoro et al 2001).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The first ultrastructural studies have in principle shown some fibrillar forms (Heinemann et al 2007;Garrone et al 1975), and some recent findings have demonstrated other peculiarities of C. reniformis collagens, including the ability of mesohyl cells to affect collagen density. This process modifies directly extracellular macromolecules or the interactions between them, comparable with the dynamics known for the mutable collagenous tissue of echinoderms (Wilkie et al 2006). These peculiarities allow a very dynamic behavior of this species that can move or drop from its substratum, showing disarranged and separated fiber bundles, and the interfibrillar filamentous material that becomes markedly disorganized and rarefied (Bonasoro et al 2001).…”
Section: Discussionmentioning
confidence: 82%
“…1b), which should provide this molecule with some more flexibility (Exposito et al 2002), and the presence of some putative glycosylation sites also in the linker peptides and in the noncollagenic regions. These sites are probably involved in the mechanisms of specific cell-matrix interactions (Schröder et al 2006) or in protein-protein noncovalent interactions occurring in the complex and so far unexplained process of stiffening of C. reniformis tissues after mechanical stimuli (Wilkie et al 2006). The marine sponge C. reniformis is in fact one of the best available models for the molecular study of Porifera collagen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine sponge Chondrosia reniformis is a common Mediterranean demosponge, which body consists of a large proportion of collagen. Due to its peculiar physical-chemical characteristics (Wilkie et al 2006), collagen derived from this sponge has been the object of study for 40 years (Garrone et al 1975;Heinemann et al 2007), and many biotechnological applications of C. reniformis collagen extracts in drug preparations (Nicklas et al 2009a, b) as well as in cosmetics (Swatschek et al 2002) have been described lately. Recently, a nonfibrillar collagen type from this sponge was cloned, and some information on the regulation of its gene expression (i.e., upregulation by soluble silicates) was also unveiled (Pozzolini et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of it are admittedly speculative, but these are testable by further experimentation. The uniqueness of echinoderm MCT cannot be exaggerated: collagenous connective tissue that is directly innervated by the motor nervous system, and that can alter drastically and reversibly its mechanical properties within short physiological timescales, appears to have evolved only in the phylum Echinodermata (though a “pre-neural” version of the phenomenon occurs in the Porifera [55]). Despite this restricted taxonomic distribution, the investigation of MCT has the potential to provide information of widespread biomedical applicability [2], [56].…”
Section: Discussionmentioning
confidence: 99%